Pensions at a glance 2015. OECD and G20 indicators (Paris, 2015)
"The 10-year anniversary edition of Pensions at a Glance highlights the pension reforms undertaken by OECD and G20 countries over the last two years. Two special chapters provide deeper analysis of first-tier pension schemes and of the impact of short or interrupted careers, due to late entry into employment, childcare or unemployment, on pension entitlements. Another chapter analyses the sensitivity of long-term pension replacement rates on various parameters. A range of indicators for comparing pension policies and their outcomes between OECD and G20 countries is also provided."